Women Activism in Yorubaland: A Catalyst for the Actualization of Gender Equality - Fasiku, Adesola Mercy (Transpublika Publisher, 2025)
The outstanding performances of Yoruba women and their activism in ancient and modern contexts have earned them significant respect in Yoruba societies. In pre-colonial Nigeria, women like Queen Aminat of Zaria and Nana Itshekiri exemplified female activism, while ancient Yoruba women such as Moremi Ajasoro, Efunroye Tinubu, and Efunsetan Aniwura made substantial impacts on their societies through determined efforts that advanced women's causes. Notably, some Yoruba kingdoms recognized women as paramount traditional rulers, including Luwo Gbagida as a woman Ooni in ancient Ile-Ife and Orompoto as a woman Alaafin in ancient Oyo kingdom, demonstrating that women occupied leadership positions in pre-colonial Nigeria. This paper evaluates concepts and activities of Yoruba women activists in post-colonial Nigeria, highlighting their achievements in adding value to women's lives and society at large. Additionally, it examines actions taken to achieve the UN-recommended 35% affirmation for women. Using thematic methods, the paper argues that women have historically gained irresistible positions, forming the basis for continued gender equality agitation. Yoruba women have remained prominent since post-colonial Nigeria, with their activities being notably impactful and elevating many to positions of repute. The study concludes that women's activism has served as a catalyst for women's development in Yoruba land and Nigeria generally. It recommends that women should be more proactive in pursuing their needs, form synergies for unified understanding and presentation, and organize conferences to develop modalities for achieving gender equality goals.